Pathways and mechanisms for product release in the engineered haloalkane dehalogenases explored using classical and random acceleration molecular dynamics simulations - Klvana, Martin; Pavlova, Martina; Koudelakova, Tana; Chaloupkova, Radka; Dvorak, Pavel; Prokop, Zbynek; Stsiapanava, Alena; Kuty, Michal; Kuta-Smatanova, Ivana; Dohnalek, Jan; Kulhanek, Petr; Wade, Rebecca C; et al. (Journal of molecular biology, 2009)
Eight mutants of the DhaA haloalkane dehalogenase carrying mutations at the residues lining two tunnels, previously observed by protein X-ray crystallography, were constructed and biochemically characterized. The mutants showed distinct catalytic efficiencies with the halogenated substrate 1,2,3-trichloropropane. Release pathways for the two dehalogenation products, 2,3-dichloropropane-1-ol and the chloride ion, and exchange pathways for water molecules, were studied using classical and random acceleration molecular dynamics simulations. Five different pathways, denoted p1, p2a, p2b, p2c, and p3, were identified. The individual pathways showed differing selectivity for the products: the chloride ion releases solely through p1, whereas the alcohol releases through all five pathways. Water molecules play a crucial role for release of both products by breakage of their hydrogen-bonding interactions with the active-site residues and shielding the charged chloride ion during its passage through a hydrophobic tunnel. Exchange of the chloride ions, the alcohol product, and the waters between the buried active site and the bulk solvent can be realized by three different mechanisms: (i) passage through a permanent tunnel, (ii) passage through a transient tunnel, and (iii) migration through a protein matrix. We demonstrate that the accessibility of the pathways and the mechanisms of ligand exchange were modified by mutations. Insertion of bulky aromatic residues in the tunnel corresponding to pathway p1 leads to reduced accessibility to the ligands and a change in mechanism of opening from permanent to transient. We propose that engineering the accessibility of tunnels and the mechanisms of ligand exchange is a powerful strategy for modification of the functional properties of enzymes with buried active sites.
Keywords: Models, Molecular; chloridy; propan; Water; Protein Structure, Tertiary; voda; zvířata; chemické modely; Hydrolases; hydrolasy; Alcohols; Propane; molekulární modely; Mutagenesis, Site-Directed; alkoholy; rekombinantní proteiny; Kinetics; mutageneze cílená; Chlorides; kinetika; Recombinant Proteins; Animals; terciární struktura proteinů; Models, Chemical